Treatment of the textile wastewater by electrocoagulation Economical evaluation - Bayramoglu, Mahmut; Eyvaz, Murat; Kobya, Mehmet (Elsevier Science Sa, 2007)
This paper presents the comparative results with respect to electrode configurations on the economic performance of treatment of textile wastewaters by electrocoagulation (EC) process. Aluminum and iron electrode materials were used as sacrificial electrode in parallel and serial connection modes. Various direct and indirect cost items including electrical, sacrificial electrodes, labor, sludge handling, maintenance and depreciation costs were considered in the calculation of the total cost per m(3) of wastewater taken from a textile plant with a capacity of 1000 m(3) per day. The results showed that monopolar-parallel mode (MP-P) was the most cost-effective for Fe and Al electrodes. These electrodes showed similar results in removal efficiency of COD and turbidity, but Fe electrode was preferred due to its low cost. pH 7 for Fe electrode and pH 5 for Al electrode were found suitable in terms of removal efficiency of COD and turbidity from textile wastewater. Meanwhile, 30 Am-2 of current density and 15 min of operating time were found to be sufficient for Fe and Al electrodes. Finally, a comparative study showed that EC was faster and more economic; consumed less material and produced less sludge, and pH of the medium was more stabilized as compared to chemical coagulation (CC) for percentage removal efficiency of COD and turbidity from textile wastewater. The treatment cost of EC at optimum conditions was 3.2 times cheaper than that of CC. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: textile wastewater; electrocoagulation; economic analysis; operating cost